Orientalizing Artifacts from Fraga dos Corvos Rock Shelter in North Portugal - Figueiredo, Elin (2013)
An unusual set of metallic artifacts with orientalizing character, attributed to a late period of the Late Bronze Age (LBA), was found in a shelter in Northern Portugal. Conventional and micro-energy dispersive X-ray fluorescence (XRF) analyses have been performed to determine the metal composition. The microstructures of some artifacts have also been studied under optical and scanning electron microscope (SEM). The results show that most of the items are made of a copper–tin alloy with low lead content and show a recrystallized grained microstructure.